Cross-cultural research methods in psychology - Matsumoto, David Ricky; Vijver, Fons J. R. van de (Culture and psychology., 2011)
"Cross-cultural research is now an undeniable part of mainstream psychology and has had a major impact on conceptual models of human behavior. Although it is true that the basic principles of social psychological methodology and data analysis are applicable to cross-cultural research, there are a number of issues that are distinct to it, including managing incongruities of language and quantifying cultural response sets in the use of scales. Cross-Cultural Research Methods in Psychology provides state-of-the-art knowledge about the methodological problems that need to be addressed if a researcher is to conduct valid and reliable cross-cultural research. It also offers practical advice and examples of solutions to those problems and is a must-read for any student of culture"--Provided by publisher.